2013
DOI: 10.1021/bc3005655
|View full text |Cite
|
Sign up to set email alerts
|

An Amphiphilic Perylene Imido Diester for Selective Cellular Imaging

Abstract: A new amphiphilic membrane marker based on a water-soluble dendritic polyglycerol perylene imido dialkylester has been designed, synthesized, and its optical properties characterized. In water it forms fluorescently quenched micellar self-aggregates, but when incorporated into a lipophilic environment, it monomerizes, and the highly fluorescent properties of the perylene core are recovered. These properties make it an ideal candidate for the imaging of artificial and cellular membranes as demonstrated by bioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 53 publications
2
66
0
Order By: Relevance
“…Similarly, Haag et al reported spherical micelles self‐assembled from perylene imino diesters (PIDEs) bearing two alkyl chains and a polyglycerol dendron of which the fluorescence quantum yield is extremely low (Figure a,b). However, PIDE 48 recovers high fluorescence in an lipophilic environment.…”
Section: Nanoparticles Based On Self‐assembled π‐Conjugated Small Molmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, Haag et al reported spherical micelles self‐assembled from perylene imino diesters (PIDEs) bearing two alkyl chains and a polyglycerol dendron of which the fluorescence quantum yield is extremely low (Figure a,b). However, PIDE 48 recovers high fluorescence in an lipophilic environment.…”
Section: Nanoparticles Based On Self‐assembled π‐Conjugated Small Molmentioning
confidence: 83%
“…a) Chemical structure of PBI 47 by Genovese et al and PIDE 48 used as b) a dye to stain membranes by Haag et al, as well as the chemical structure of Pe‐Cbl 49 and 50 by Singh et al and Zhao et al, respectively, which have been explored as c) single‐component perylene‐based drug delivery system for photocontrolled delivery of an anticancer drug. b) Reproduced with permission . Copyright 2013 , American Chemical Society.…”
Section: Nanoparticles Based On Self‐assembled π‐Conjugated Small Molmentioning
confidence: 99%
“…However, these dyes still have aggregation‐related issues that lead to fluorescence quenching, and therefore, little success has been achieved regarding specificity . Notably, PBI absorption and emission spectral properties that are well‐matched with commonly used lipophilic probes have rarely been exploited for LD imaging either in vivo or in vitro.…”
Section: Methodsmentioning
confidence: 99%
“…1 Among the different chains used, it has been shown that branched alkyl chains tend to soften the π-conjugated materials to a greater extent than attaching linear n alkyl chains and allow to tune both the molecular-scale and bulk material properties of soft matter. 7 Additionally, due to their excellent photophysical properties, great efforts have been dedicated to the production of highly water-soluble perylene derivatives 8−10 in order to apply them in different areas such as in the field of cellular imaging, 11 in vitro staining of cells and proteins, 12 in the aqueous dispersion of single wall carbon nanotubes, 13 or in the development of multilayer films for photophysical studies. 14 On the other hand, by using suitable flexible chains as substituents in PBI derivatives, it has been possible to induce liquid crystallinity.…”
Section: ■ Introductionmentioning
confidence: 99%